Study of the behavior of sugarcane bagasse submitted to cutting (2015)
The aim of this work was to study the behavior of sugarcane bagasse submitted to cutting, as a function of its moisture content, angle of the blade edge and cutting speed. The specific cutting energy and peak cutting force were measured using an experimental facility developed for this series of experiments. An analysis of the results of the full factorial experimental design using a statistical analysis of variance (ANOVA) was performed. The response surfaces and empirical models for the specific cutting energy and peak cutting force were obtained using statistical analysis system software. Low angle of the blade edge and low moisture content are, in this order, the most important experimental factors in determining a low specific cutting energy and a low peak cutting force respectively. The best cutting conditions are achieved for an angle of blade edge of 20.8° and a moisture content of 10% w. b. The results of this work could contribute to the optimal design of sugarcane bagasse pre-treatment systems.